A novel end‐to‐end deep learning solution for coronary artery segmentation from CCTA. Issue 11 (11th July 2022) - Dong, Caixia; Xu, Songhua; Li, Zongfang
Abstract: Purpose: Coronary computed tomographic angiography (CCTA) plays a vital role in the diagnosis of cardiovascular diseases, among which automatic coronary artery segmentation (CAS) serves as one of the most challenging tasks. To computationally assist the task, this paper proposes a novel end‐to‐end deep learning‐based (DL) solution for automatic CAS. Methods: Inspired by the Di‐Vnet network, a fully automatic multistage DL solution is proposed. The new solution aims to preserve the integrity of blood vessels in terms of both their shape details and continuity. The solution is developed using 338 CCTA cases, among which 133 cases (33865 axial images) have their ground‐truth cardiac masks pre‐annotated and 205 cases (53365 axial images) have their ground‐truth coronary artery (CA) masks pre‐annotated. The solution's accuracy is measured using dice similarity coefficient (DSC), 95th percentile Hausdorff Distance (95% HD), Recall, and Precision scores for CAS. Results: The proposed solution attains 90.29% in DSC, 2.11 mm in 95% HD, 97.02% in Recall, and 92.17% in Precision, respectively, which consumes 0.112 s per image and 30 s per case on average. Such performance of our method is superior to other state‐of‐the‐art segmentation methods. Conclusions: The novel DL solution is able to automatically learn to perform CAS in an end‐to‐end fashion, attaining a high accuracy, efficiency and robustness simultaneously.